Study of gain, noise, and collection efficiency of GaAs SAM-APDs single pixel. (1st December 2022) - Colja, M.; Cautero, M.; Menk, R.H.; Palestri, P.; Gianoncelli, A.; Antonelli, M.; Biasiol, G.; Zilio, S.D.; Steinhartova, T.; Nichetti, C.; Arfelli, F.; De Angelis, D.; et al.
Abstract: III-V-compound semiconductors offer many advantages over silicon-based technologies traditionally used in solid-state photodetectors, especially in hard X-ray applications that require high detection efficiency and short response times. Amongst them, gallium arsenide (GaAs) has very promising characteristics in terms of X-ray absorption and high carrier velocity. Furthermore, implementing charge-multiplication mechanisms within the sensor may become of critical importance in cases where the photogenerated signal needs an intrinsic amplification before being acquired by the front-end electronics. This work reports on the experimental characterization by means of lasers and synchrotron radiation of gain, noise, and charge collection efficiencies of GaAs avalanche photodiodes (APDs), realized by molecular beam epitaxy (MBE), featuring separate absorption and multiplication regions (SAM) and different absorption region thicknesses. These devices have been fabricated to investigate the role of the thickness of the absorption region and of possible traps or defects at the metal-semiconductor interfaces in the collection efficiency in order to lay the groundwork for the future development of thicker GaAs devices for detection of hard X-rays.